2014
DOI: 10.5603/cj.a2013.0087
|View full text |Cite
|
Sign up to set email alerts
|

Training surgeon status is not associated with an increased risk of early or late mortality after isolated aortic valve replacement surgery

Abstract: Background: Few studies have addressed the effect of "trainee surgeon" status on outcomes after isolated aortic valve replacement (AVR). Methods and Results: (Cardiol J 2014; 21, 2: 183-190)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…There were no differences in postoperative complications between the two groups when the incidence of resternotomy for bleeding/tamponade, stroke, myocardial infarction, ITU stay, pacemaker implantation, new renal failure requiring dialysis, and total hospital stay 24–26 …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…There were no differences in postoperative complications between the two groups when the incidence of resternotomy for bleeding/tamponade, stroke, myocardial infarction, ITU stay, pacemaker implantation, new renal failure requiring dialysis, and total hospital stay 24–26 …”
Section: Resultsmentioning
confidence: 97%
“…There were no mortality differences between TS and FTS. The in‐hospital mortality for TS is reported as 2% versus 6% in FTS cohorts 24–26 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, only 2 studies reported on the comparison of mid- and long-term mortality between trainees’ and consultants’ cases and no difference was found [ 11 , 12 ]. Compared to these studies, we reported on longer mean follow-up outcome and demonstrated that the equipoise between trainees’ and consultants’ cases persists during a longer follow-up.…”
Section: Discussionmentioning
confidence: 99%